New records of Trichoceridae (Diptera) from the island of Mallorca ​ - Petrašiūnas, Andrius (Biodivers Data J, 2016)
Abstract. BACKGROUND: The Trichoceridae are a small family distributed mainly in the Holarctic Region, most of which are associated with cold seasons and even snow. From the Iberian peninsula, 5 species have been recorded; however only a single previous occurence record exists from the Balearic islands. NEW INFORMATION: In this paper we present new records of two species from Mallorca, of which Trichocera (Saltrichocera) saltator (Harris, 1776) has not previously been recorded from the Balearic islands. Trichocera (Saltrichocera) annulata Meigen, 1818 is recorded for the first time from Mallorca. We furthermore discuss the species' distributions within the Mediterranean region and report new morphological data for the Mallorca island form of T. saltator.